2022
DOI: 10.1096/fj.202200792rr
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal levels of mitochondrial Ca 2+ channel proteins in plasma neuron‐derived extracellular vesicles of early schizophrenia

Abstract: Structural alterations or quantitative abnormalities of some mitochondrial ion channels and exchangers are associated with altered neuronal functions and increased susceptibility to mental illness. Here we have assessed levels of functionally prominent mitochondrial calcium ion channel proteins in plasma neuron‐derived extracellular vesicles (NDEVs) of living patients with first episodes of psychosis (FP) and matched controls (Cs). NDEVs were enriched with an established method of precipitation and immunoabsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Plasma humanin decreases with age in humans and mice [ 43 ], and upon replenishment, cognition in aged mice is improved [ 44 ]. Humanin mRNA in plasma EVs has been found decreased in AD compared to control individuals [ 45 ], whereas protein levels of humanin in NDEVs have been found decreased in multiple neuropsychiatric disorders [ 46 , 47 ]. Interestingly, physical activity increases humanin in plasma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma humanin decreases with age in humans and mice [ 43 ], and upon replenishment, cognition in aged mice is improved [ 44 ]. Humanin mRNA in plasma EVs has been found decreased in AD compared to control individuals [ 45 ], whereas protein levels of humanin in NDEVs have been found decreased in multiple neuropsychiatric disorders [ 46 , 47 ]. Interestingly, physical activity increases humanin in plasma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between the groups in the amount and size of exosomes [ 118 ]. Again by the same group, a significant decrease in mitochondrial functional protein levels such as ATP synthase, mitofusin 2, and cyclophilin in astrocyte and neuron-derived exosomes in patients with first-episode psychosis in astrocyte-derived extracellular vesicles and NDEVs [ 119 ] and altered levels of mitochondrial calcium ion channel proteins such as an increased level of CACNA- 1C and decreased levels of LETM1, NCLX, SLC24A6, and TRPM4 in plasma NDEVs of patients with first-episode psychosis [ 120 ] have been reported. In another study, it was shown that Aβ42 levels in astrocyte-derived exosomes (ACE) were higher in patients with schizophrenia compared to controls, and high exosome ACE-P-T181-tau levels in the whole sample were associated with impaired executive functions [ 121 ].…”
Section: Egms and Psychiatric Disordersmentioning
confidence: 99%
“…Theoretically, uTEVs may also contain EVs derived from other CNS cells, such as neurons and various types of glial cells, including microglia and oligodendrocytes, which could be isolated using similar methods. For other types of BDEVs, such as NDEVs, L1 cell adhesion molecule (L1CAM) is commonly used as a marker [55][56][57] . However, L1CAM expression is also detected in the kidney 58 , potentially compromising the purity of urinary L1CAM + EVs that are truly derived from CNS.…”
Section: Discussionmentioning
confidence: 99%